1990
DOI: 10.1111/j.1365-2125.1990.tb03618.x
|View full text |Cite
|
Sign up to set email alerts
|

The measurement of haloperidol and reduced haloperidol in hair as an index of dosage history.

Abstract: 1. We report a method for measuring the concentrations of haloperidol (HL) and its major active metabolite, reduced haloperidol (RHL), in human scalp hair. 2. Hair samples were obtained from 59 patients who had been taking HL at fixed daily doses for more than 4 months and whose compliance was good. A morning pre‐dose plasma sample was also obtained from 48 of these patients. 3. The concentrations of HL and RHL in hair (ng mg‐1 hair) correlated significantly both with the daily dose (micrograms kg‐1 body weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 26 publications
0
33
0
Order By: Relevance
“…Therefore, the condition of MS analysis was changed from full MS measurement to SIM. The selected ions used for the determination of TZ, 1-HT, 4-HT, 1,4-diHT, and 1-HTd 4 were the quasi-molecular ions, m/z 343, 359, 359, 375, and 363, respectively. Relatively stable baseline was obtained from the SIM.…”
Section: Determination Of Tz and The Metabolites In Rat Hair Shafts Amentioning
confidence: 99%
“…Therefore, the condition of MS analysis was changed from full MS measurement to SIM. The selected ions used for the determination of TZ, 1-HT, 4-HT, 1,4-diHT, and 1-HTd 4 were the quasi-molecular ions, m/z 343, 359, 359, 375, and 363, respectively. Relatively stable baseline was obtained from the SIM.…”
Section: Determination Of Tz and The Metabolites In Rat Hair Shafts Amentioning
confidence: 99%
“…No relationships could be established between opiate levels in hairs and morphine administration in carcinoma patients [23]. On the other hand, some papers reported significant relationships for digoxine, cocaine, phencyclidine, cannabis, morphine [5], haloperidol [16], nicotine [19], or amitriptyline [15]. …”
Section: Resultsmentioning
confidence: 95%
“…We have shown that an ingested drug, whether administered continuously or intermittently, is deposited in hair in proportion to the dose and that it is captured there, moving outwards along the shaft as the hair grows [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Therefore, it may be possible to consider a strand of hair as a "tape-recorder," which continuously stores all the data about the drug exposure of individual over the past several months, or possibly years.…”
Section: Discussionmentioning
confidence: 99%
“…Haloperidol and reduced haloperidol were simultaneously measured according to the method previously reported [9]. The HPLC system consisted of a system controller, integrator, pump, autoinjector, column oven (SCL-6B, C-R4A, LC-6A, SIL-6B, CTO-6A, respectively; Shimadzu, Kyoto, Japan), and a Coulochem detector with a guard cell and a high-sensitivity analytical cell (5100A, 5020 and 5011, respectively; ESA, Bedford, MA, USA).…”
Section: Chromatographymentioning
confidence: 99%